Offshore wind farms changed the spatial distribution of chlorophyll-a on the sea surface - Lu, Zhengyu; Li, Guoqing; Liu, Zhe; Wang, Luyan (Frontiers in Marine Science, 2022)
Offshore wind farms (OWFs) have developed rapidly in recent years. However, it is difficult to accurately evaluate their impact on marine ecosystems and the marine environment due to the complexity of marine dynamic monitoring and various marine environment evaluation indicators. The spatial distribution of chlorophyll-a (Chl-a) on the surface of seawater is one of basic spatial information of the sea area, which is the key determines the distribution and productivity of offshore biological resources at different spatial levels. Evaluating the impact of OWFs on the spatial distribution of Chl-a is of significance but the research carried out to date has been scarce. In this study, 682 Landsat images were selected from 1990 to 2021 as well as 38 OWFs from around the world as the research areas. The spatial distribution of Chl-a on the sea surface was calculated using the O’Reilly band ratio OC2 algorithm and HU color index (CI) algorithm and the influence of OWFs on the spatial distribution pattern of Chl-a was determined by using the global and local Moran Indexes. Among the 38 wind farms, it was found that: (1) the spatial autocorrelation of Chl-a concentration at 37 wind farms increased after the construction of the wind turbines; (2) the spatial distribution pattern of Chl-a at 28 wind farms showed pronounced aggregation after the construction of the wind turbines. Therefore, it was determined that the construction of OWFs will change the spatial distribution pattern of Chl-a, which may affect the original balance of local marine ecosystems.